Chilling and forcing temperatures interact to predict the onset of wood formation in Northern Hemisphere conifers. (6th January 2019) - Delpierre, Nicolas; Lireux, Ségolène; Hartig, Florian; Camarero, Jesus Julio; Cheaib, Alissar; Čufar, Katarina; Cuny, Henri; Deslauriers, Annie; Fonti, Patrick; Gričar, Jožica; Huang, Jian‐Guo; Krause, Cornelia; et al.
Abstract: The phenology of wood formation is a critical process to consider for predicting how trees from the temperate and boreal zones may react to climate change. Compared to leaf phenology, however, the determinism of wood phenology is still poorly known. Here, we compared for the first time three alternative ecophysiological model classes ( threshold models, heat‐sum models and chilling‐influenced heat‐sum models) and an empirical model in their ability to predict the starting date of xylem cell enlargement in spring, for four major Northern Hemisphere conifers ( Larix decidua, Pinus sylvestris, Picea abies and Picea mariana ). We fitted models with Bayesian inference to wood phenological data collected for 220 site‐years over Europe and Canada. The chilling‐influenced heat‐sum model received most support for all the four studied species, predicting validation data with a 7.7‐day error, which is within one day of the observed data resolution. We conclude that both chilling and forcing temperatures determine the onset of wood formation in Northern Hemisphere conifers. Importantly, the chilling‐influenced heat‐sum model showed virtually no spatial bias whichever the species, despite the large environmental gradients considered. This suggests that the spring onset of wood formation is far less affected by local adaptation than by environmentally driven plasticity. In a context of climate change, we therefore expect rising winter–spring temperature to exert ambivalent effects on the spring onset of wood formation, tending to hasten it through the accumulation of forcing temperature, but imposing a higher forcing temperature requirement through the lower accumulation of chilling. Abstract : A temperature sum model influenced by chilling accumulation predicts the spring onset of xylem enlargement across temperate and boreal latitudes, in four major Northern Hemisphere conifers. This model outperformed heat‐sums and threshold models. On the figure, plots per species show predicted (coloured lines) and observed (grey dots) xylem onset dates, sorted by temperatures during the January–June period. The central plot shows the species‐specific relation between chilling and forcing accumulation.